Ground Vehicle for Fire Fighting Purpose in Hazardous Environment - Tan, CheeFai; Alkahari, M.R.; Liew, S.M.; Said, M.R.; Ranjit, S.S.S.; Kher, V.K. (2012)
In this project, design, development and performance of a wirelessly controlled Fire Fighting Ground Vehicle (FIGOV) is described. FIGOV is a wireless control mobile machine that is equipped with firefighting equipment. It carries high density camera, sensors, communication equipment, firefighting equipment and other loads in order to control fire and perform victim searching task. The machine is wirelessly controlled via mobile computer. The nozzle of the machine can be directed at different angle and can be elevated in order to control fire at different height. FIGOV can be used to reduce the risks faced by fire fighters in performing their duties. This is due to the fact to the current fire fighting techniques require fire fighters to intervene in hazardous conditions. Working at very high temperature, dusty, low humidity, dangerous and others are among usual working conditions associated with fire fighting. Study conducted showed that the machine can be successfully be used in real fire fighting process. Effective use of the machine also can avoid direct contact of human especially fire fighter with radioactive or hazardous materials that may have immediate or long-term effects on health as well as fatigue to human.